ANALISIS SPASIAL INDEKS KEKERINGAN DI DAERAH ALIRAN SUNGAI (DAS) KAMPAR PROVINSI RIAU - Novreta Ersyi Darfia; Widdya Rahmalina2 (Jurnal Infrastruktur, 2019)
Global warming has increased the frequency and intensity of extreme climate events such as drought. Mitigation to reduce the impact caused by drought needs to be done. However, information about land drought is still lacking at this time. Information about surface conditions is needed both in the form of numerical data and spatial data. Along with technological advances, a spatial information area can be done easily. Geographical information systems have a very good ability to visualize spatial data and its attributes. This study aims to map the distribution of drought indices in the Kampar River Basin (DAS) of Riau Province. It is hoped that this research can provide spatial information on the spread of drought indexes so that action can be taken to avoid or reduce the impact of such drought. There are two main analyzes conducted in this study, namely the analysis of the drought index using the KBDI method and the spatial analysis of the drought index of the KBDI method. Spatial analysis shows the results that the nature of drought at the study site is dominated by the nature of